Revolutionizing Contract Lifecycle Management: The Impact of AI-Driven Automation - Rincy Soman (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Contract Lifecycle Management (CLM) is experiencing a revolutionary transformation through the integration of artificial intelligence technologies. This comprehensive article explores how AI-driven automation is reshaping the entire contract management landscape, from document creation to risk assessment and compliance monitoring. It examines the technical foundations of AI-powered document creation, including advanced language models, natural language processing, and semantic analysis capabilities. The article investigates the evolution of version control systems, workflow automation frameworks, and sophisticated risk assessment methodologies. It delves into machine learning pipelines for continuous improvement and explores future directions in CLM, including blockchain integration, enhanced natural language understanding, and cross-language contract management capabilities. Through detailed analysis of real-world implementations and industry research, this article demonstrates how AI-driven CLM solutions are enabling organizations to achieve significant improvements in operational efficiency, compliance accuracy, and risk management while reducing costs and manual intervention in contract processing.